2020
DOI: 10.1111/jnu.12538
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Parents Seeking Care From Emergency Services Due to Fever in Children

Abstract: Purpose To explore the behavior of parents, with and without health training, seeking care from emergency services due to their child’s fever. Design and Setting A qualitative study based on Grounded Theory using a triangulated sample (theoretical sampling and snowball sampling) of parents of children 0 to 12 years old who received care for fever in the emergency primary care services of two Spanish municipalities. Methods Data saturation was achieved after eight focus groups segmented by gender, place of resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…Fever as the body's physiological response (Green, Krafft, et al, 2021) is a body temperature of 37.5°C and above by armpit measurement according to the World Health Organization (WHO, 1993). Fever is one of the main reasons why patients seek healthcare in both high‐income and low‐ and middle‐income countries, (Green, Webb, et al, 2021; Pitoli et al, 2021; Villarejo‐Rodríguez & Rodríguez‐Martín, 2020). It is an important cause of morbidity and mortality (Fernandez‐Carballo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fever as the body's physiological response (Green, Krafft, et al, 2021) is a body temperature of 37.5°C and above by armpit measurement according to the World Health Organization (WHO, 1993). Fever is one of the main reasons why patients seek healthcare in both high‐income and low‐ and middle‐income countries, (Green, Webb, et al, 2021; Pitoli et al, 2021; Villarejo‐Rodríguez & Rodríguez‐Martín, 2020). It is an important cause of morbidity and mortality (Fernandez‐Carballo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that implementing fever management education programs effectively improves families' knowledge and significantly reduces inappropriate practices (Alqudah et al, 2014; Chiappini et al, 2017; NICE, 2019; Ong et al, 2018; Peetoom et al, 2016). While studies on the knowledge level, attitudes, and behaviours of parents about fever extend from the 1980s to the present (Schmitt, 1980), studies on determining what mothers experience emotionally in this process, people who help and support mothers at home and what difficulties they experience are limited (Macit, 2020; Pitoli et al, 2021; Villarejo‐Rodríguez & Rodríguez‐Martín, 2020). In a current systematic review (Vicens‐Blanes et al, 2022), in which 17 studies were examined, in addition to the fact that parents see fever as a non‐harmful sign in itself, it is stated that it is still a condition that requires urgent intervention and the perceived need to reduce temperature is the primary goal of their approach.…”
Section: Introductionmentioning
confidence: 99%
“…Similar measures must be taken for educating the parents in Latvia, this could be achieved by creation of a universal guidance including evidence-based and easily understandable information, which could be distributed by doctors in primary care as well as emergency departments, and also made available online. In addition to information on fever and its management, the information needs on the current episode of febrile illness, such as the cause of fever, seriousness of the disease, and the potential dangers of fever should be satisfied [275,277,330].…”
Section: Consideration Of Parental Concern and Fever-related Anxietymentioning
confidence: 99%